2021
DOI: 10.1002/adom.202002238
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dye Degradation through Multi‐Particle Confinement in a Porous Silicon Substrate: A Highly Efficient, Low Band Gap Photocatalyst

Abstract: A platform is introduced for fabrication of a reusable and highly efficient low band gap photocatalyst by confining gold nanoparticles (AuNPs) in the pores of a nanopatterned Si monolith (AuNSM). Due to their size, a maximum of two AuNPs can assemble in a single pore, thus preventing agglomerations. Their access to the analyte provides more active sites for redox reaction, leading to enhanced efficiency. While proximity of nanoparticles enhances coupling efficiency, confinement prevents rapid recombination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Upon the infiltration of weak polyion block domains with metal ions (Ni + , Al 3+ and Cr 2+ ), well-defined metal-oxide nanodots and/or nanowires were obtained and used to define etch masks for pattern transfer [ 217 ]. For instance, we recently reported the use of a high-contrast etch mask for pattern transfer into silicon substrates through ICP/RIE etching for the development of vertically coupled plasmonic arrays for use in surface enhanced Raman scattering [ 213 ], anti-reflective surfaces, and photocatalysts [ 218 ].…”
Section: Block Copolymer Systems Based On Weak Polyelectrolytesmentioning
confidence: 99%
“…Upon the infiltration of weak polyion block domains with metal ions (Ni + , Al 3+ and Cr 2+ ), well-defined metal-oxide nanodots and/or nanowires were obtained and used to define etch masks for pattern transfer [ 217 ]. For instance, we recently reported the use of a high-contrast etch mask for pattern transfer into silicon substrates through ICP/RIE etching for the development of vertically coupled plasmonic arrays for use in surface enhanced Raman scattering [ 213 ], anti-reflective surfaces, and photocatalysts [ 218 ].…”
Section: Block Copolymer Systems Based On Weak Polyelectrolytesmentioning
confidence: 99%
“…It is important to note that, besides the focus of the development of magnetic nanocomposites for water and wastewater treatment, new recent trend of development of new materials is emerging. For example, Mir et al [138] studied how confining AuNPs in a porous Si template can significantly enhance the photocatalytic activity of MO. The pores prevent agglomeration of nanoparticles and eliminate the need for any functionalization.…”
Section: Mixed-metal Ferrites and Nanocompositesmentioning
confidence: 99%
“…The results showed that the recyclable, low-band gap photocatalytic system has economic and environmental advantages that promote implementation of catalytic and separation processes in continuous flow mode, with the advantages associated with easier phase separation and product recovery, enhanced safety, and easier operation [138].…”
Section: Mixed-metal Ferrites and Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations